1999
DOI: 10.1088/0964-1726/8/5/304
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed optical fibre Fabry-Perot sensors for strain metrology

Abstract: This paper demonstrates the feasibility of multiplexing several optical fibre-based Fabry-Perot sensors in series for strain metrology. White-light interferometry was employed using the laser-referenced Michelson interferometer of a standard Fourier-transform spectrometer as a receiving (interrogating) interferometer. The primary aim was to demonstrate that at least six fibre Fabry-Perot transducer interferometers (sensors) can be multiplexed in series. A prerequisite for this sensor system is that each sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Air cavities of greater than 20 μm are required to eliminate misalignment of the cavity endfaces; lengths of 30–40 μm were selected to provide both good temperature sensitivity and low coupling loss. The fiber cavity length must be greater than the air cavity length by enough distance to allow sufficient frequency separation of the coupled air cavity, fiber cavity, and air/fiber combination signals, similar to the demodulation of a frequency-based multiplexed sensor, as described elsewhere [ 38 , 39 ]. Cavities in the range of 100–150 μm are sufficient to meet this requirement.…”
Section: Methodsmentioning
confidence: 99%
“…Air cavities of greater than 20 μm are required to eliminate misalignment of the cavity endfaces; lengths of 30–40 μm were selected to provide both good temperature sensitivity and low coupling loss. The fiber cavity length must be greater than the air cavity length by enough distance to allow sufficient frequency separation of the coupled air cavity, fiber cavity, and air/fiber combination signals, similar to the demodulation of a frequency-based multiplexed sensor, as described elsewhere [ 38 , 39 ]. Cavities in the range of 100–150 μm are sufficient to meet this requirement.…”
Section: Methodsmentioning
confidence: 99%
“…The advantages of optical fibre-base sensor systems include [ 27 ]: (i) the circular cross-section of optical fibres with diameters in the range 20–200 micrometres. This makes it relatively easy to embed them within the preforms at the time of manufacturing [ 28 ]; (ii) the surface chemistry of optical fibres is receptive to conventional surface treatments such as silane coupling agents [ 29 ]; (iii) they are immune from electromagnetic interference, hence, unlike their electrical counterparts, they can be used in environments with high electrical potentials; (iv) a unique characteristic is the possibility of monitoring multiple parameters on a single optical fibre [ 30 ]; (v) distributed sensing is also a practical reality [ 31 ]; and (vi) a wide range of optical fibre types are available commercially, thus appropriate compositions can be selected to suit specified end-use applications [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of using an EFPI sensor design for monitoring strain in tandem with temperature logging via fluorescence-decay has also been demonstrated [20]. Singh et al [21] reported the feasibility of multiplexing a number of EFPI sensors where the interrogation was carried out using a conventional Fourier transform infrared spectrometer.…”
Section: Introductionmentioning
confidence: 99%